Drying kinetics of processed natural coffee with high moisture content - Siqueira, Valdiney Cambuy; Borém, Flávio Meira; Alves, Guilherme Euripedes; Isquierdo, Eder Pedroza; Pinto, Afonso Celso Ferreira; Ribeiro, Diego Egidio; Ribeiro, Fabiana Carmanini (Coffee Science - ISSN 1984-3909, 2017)
The present study proposes a new processing and drying method and evaluates the behavior of grains subjected to this process through the water reduction rate and the adjustment of different mathematical models. Mature beans were divided into three batches. The first batch was continuously dried at 40±1 °C. The second batch consisted of natural coffee dried to moisture contents of 0.56±0.02, 0.41±0.02, 0,28±0.02 and 0.20±0.02 decimal (dry basis, d.b.), followed by processing and continuous drying at 35±1 ºC and 40±1 ºC. For all parcels, the drying process was ended when the coffee beans reached the moisture content level of 0.12±0.05 (d.b.). The third batch corresponded to the continuous drying of hulled and demucilated coffee at 40±1 °C. The experimental data were adjusted to ten mathematical models used to represent the drying of agricultural products. The grain water reduction rate was also evaluated. We concluded that the water reduction rate was highest for the drying temperature of 40±1 °C, especially at higher moisture contents. The total drying time for processed coffee with high moisture content was significantly reduced compared with the total drying time of natural coffee. The Midilli model satisfactorily describes the drying kinetics of processed coffee.